2018
DOI: 10.1590/2177-9465-ean-2018-0128
|View full text |Cite
|
Sign up to set email alerts
|

Aging with physical disabilities: experience intersected by stigma, social isolation and finitude

Abstract: Objective: To understand the experience from a perspective of elderly people with physical disabilities. Method: Qualitative study that interviewed 15 people from the Mato Grosso Association of Disabled Person. Testimonies were obtained from 2016 July to 2017 June in the metropolitan region of Cuiabá/Brazil. Data were organized in thematic categories and analyzed through social phenomenology of Alfred Schütz. Results: It was evidenced that the stigma intersects the experience of the physical deficiency inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…Participants felt not just stigmatised by their mobility challenge, but also by their age, which may also have contributed to the lack of integration between their mobility challenges to their self‐identity. It is known that older people living with mobility challenges may be particularly stigmatised, as they are branded by both their age and their disability status (Martins et al, 2018). This situation is not different in Brazil, where ageing and disability have negative cultural connotations due to the high appreciation of youth and body aesthetics (Andrade, 2011; Couto & Koller, 2012; Goldani, 2010; Vasconcelos, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Participants felt not just stigmatised by their mobility challenge, but also by their age, which may also have contributed to the lack of integration between their mobility challenges to their self‐identity. It is known that older people living with mobility challenges may be particularly stigmatised, as they are branded by both their age and their disability status (Martins et al, 2018). This situation is not different in Brazil, where ageing and disability have negative cultural connotations due to the high appreciation of youth and body aesthetics (Andrade, 2011; Couto & Koller, 2012; Goldani, 2010; Vasconcelos, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…O último tema descodificado "Superação das dificuldades", proporcionou aos participantes dos Círculos de Cultura a manifestarem seus sentimentos, que estão presentes na vida de muitos idosos. Mostraram-se felizes em poder compartilhar suas vivências, dentre elas as suas dificuldades e a importância de participarem de grupos que despertam para o conhecimento e reflexões sobre suas vidas, Graziela Bernardo, Dayane Potgurski, Daniela Silva, Janaina Souza, Ivonete Heidemann, Aline Arakawa-Belaunde significativo na experiência vivenciada diante o processo de envelhecimento 13 .…”
Section: Desvelamento Críticounclassified
“…Researchers have found the intersection between disability, isolation, and aging complex (Martins et al 2018). As people with physical disabilities become older, their isolation may peak or exacerbate as their mobility declines (Martins et al 2018).…”
Section: Causes Of Social Isolationmentioning
confidence: 99%
“…Researchers have found the intersection between disability, isolation, and aging complex (Martins et al 2018). As people with physical disabilities become older, their isolation may peak or exacerbate as their mobility declines (Martins et al 2018). For instance, a study of isolation and loneliness in the elderly in the UK found that over a quarter of elderly individuals reported that they were not involved in their community because they were disabled or were taking care of someone who was disabled (Wigfield and Alden 2018).…”
Section: Causes Of Social Isolationmentioning
confidence: 99%